Functions of music, focused on the context of music listening, and psychological well-being in late adolescence regarding gender differences - Habe, Katarina; Dobrota, Snježana; Reić Ercegovac, Ina (Frontiers in Psychology, 2023)
Late adolescences, as a developmentally challenging transitional period between childhood and adulthood, provides a number of pressures that impact well-being of youth. Among approaches for facilitating well-being, music is reported to be one of the most effective ones, which was especially proven during Covid-19 pandemic. Given the significance of music and music listening in late adolescence, our study sought to examine the relationship between psychological well-being and music listening among university students (N = 603; Nfemale = 356, Nmale = 247) with a focus on the social, intrapersonal, and sociocultural context of music listening. The RESPECT music scale, the SPWB, and the PANAS were used to measure positive and negative affect as well as the six components of psychological well-being. The findings revealed that, while there were no gender differences in the sociocultural setting, females reported to listen to music more frequently than males in intrapersonal and social contexts. In two areas, female students rated their psychological well-being higher than male students: personal growth and positive relationships with others. They also reported experiencing positive and negative affect more frequently than men. Regression analyses revealed that the functions of music explained only a small amount of the variance in psychological well-being. Specifically, music listening in a social and sociocultural context significantly explained two aspects of psychological well-being: personal growth and positive relations with others. The intrapersonal context of music listening predicted a positive affect, while the social context predicted a negative affect. Our study highlights several implications of music listening in youth regarding gender either in everyday activities or in educational and clinical setting.